Analisis Framing Pemberitaan Pencabutan Investasi Miras dalam Perpres 10/2021 di Media Kompas.com dan Liputan6.com - Putri Antika Rahma Dewi; Iswahyudi (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
The revocation of alcohol investment in Attachment III to Presidential Decree Number 10 of 2021 is a public policy phenomenon that had become a trending topic and was widely reported by online media in Indonesia in 2021. The online media that highlighted the revocation of alcohol investment were Kompas.com and Liputan6.com. In this case, the same event can be treated and framed differently by an online media. Therefore, this study aims to describe Kompas.com and Liputan6.com in constructing the reality of the news using syntactic, script, thematic and rhetorical framing and to compare the framing of the two media in reporting on the revocation of alcohol investment. This study uses a qualitative approach with framing analysis method. The framing analysis used is the Zhongdang Pan and Kosicki models. From the results of this study, it can be concluded that the construction of news reality built by Kompas.com emphasizes the aspects of choosing news sources, quotes from news sources and the 5W+1H pattern. The construction of news reality built by Liputan6.com emphasizes aspects of headlines, leads and quotes from news sources. The framing comparison between Kompas.com and Liputan6.com can be seen from the analysis of the overall news. Kompas.com is framing this revocation case from a legal perspective, the reporting side is more critical and tends to think that this revocation is not according to procedure. While Liputan6.com is framing this case from various perspectives, it seems that it places more emphasis on responses and suggestions regarding this revocation and tends to judge that this revocation is appropriate and in accordance with the values ​​of Pancasila.